Completion rate of latent tuberculosis infection treatment in patients aged 65 years and older. (October 2019) - Noh, Chang Suk; Kim, Hwan Il; Choi, Hayoung; Kim, Youlim; Kim, Cheol-Hong; Choi, Jeong-Hee; Hyun, In Gyu; Baek, Moon Seong
Abstract: Introduction: There are insufficient data on the treatment of latent tuberculosis infection (LTBI) in elderly patients. We investigated the completion rate of treatment in elderly LTBI patients. Methods: A retrospective multicentre study was conducted at five university hospitals in South Korea. We reviewed the electronic medical records of patients aged 65 years and older who were diagnosed with LTBI via positive interferon-gamma release assay results between January 2016 and December 2018. Treatment completion was defined as ingestion of more than 80% of all prescribed medications without loss to follow-up. Results: During the study period, 127 LTBI patients aged 65 years and older visited outpatient department. Among them, 77 patients aged 65–78 years (median age, 69 years [interquartile range, 66–71 years]) who received LTBI treatment were analysed. Common reasons for IGRA testing in elderly patients were health-care worker (n = 33, 42.9%) and household contact with infectious TB patients (n = 18, 23.4%). The overall completion rate of LTBI treatment was 83.1% (n = 64), and the completion rate of 3-month isoniazid plus rifampin regimen was 88.4%. Adverse effects were reported in 23 patients (29.9%), and an increase in aminotransferase level was the most common adverse effect (n = 11, 14.3%). Three patients (3.9%) with the adverse effect discontinued treatment and 10 (13.0%) patients were lost to follow-up. Conclusions: LTBI treatment in patients aged 65–78 years was relatively well tolerated. In LTBI treatment in elderly patients, the majority of discontinuation of treatment was due to loss to follow-up rather than adverse effects of anti-TB medications. Highlights: Treatment of latent tuberculosis infection in patients aged 65–78 years is relatively well tolerated. The completion rate of the 3-month isoniazid plus rifampin regimen in elderly patients was 88.4%. The primary cause of cessation of treatment was loss to follow-up rather than adverse effects of anti-tuberculosis drugs.